KIAN MENDUNIA TREN WISATA HALAL: RELIGIUSITAS DAN EFIKASI DIRI BERWISATA - Anwar L Nata, Andrian (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2022)
Developing halal tourism is considered to be very good tourism progress in terms of economic, social and cultural conditions for a region in Indonesia and even the world which indirectly feels the impact both economically and socially. This research is a library research. Data collection was carried out using secondary data derived from books, literature, journals, written works, and the internet. Religiosity and travel self-efficacy have a role in the interest in halal travel which can be seen from the generation of Muslim tourists, namely a high level of religiosity will have a desire to choose to visit halal tourist destinations and a high tendency for Muslim tourists to experience new experiences and adventures in tourist attractions. lawful. The trend of halal tourism is increasingly global, this can be seen from the many travel agents who are tempted to enter the halal tourism market where the potential for halal tourists is truly amazing.